Hello, BrianU!
We can do this one head-on if we know that: \(\displaystyle \,\tan^2\theta\,+\,1\:=\:\sec^2\theta\)
\(\displaystyle \text{Prove: }\L\frac{(\sec\theta\,-\tan\theta)^2\,+\,1}{\csc\theta(\sec\theta\,-\,\tan\theta}\)\(\displaystyle \;=\;2\cdot\tan\theta\)
The left side is: \(\displaystyle \L\,\frac{\sec^2\theta\,-\,2\cdot\sec\theta\cdot\tan\theta \,+\,\overbrace{\tan^2\theta\,+\,1}}{\csc\theta(\sec\theta\,-\,\tan\theta)}\;=\;\frac{\sec^2\theta\,-\,2\cdot\sec\theta\cdot\tan\theta\,+\,\sec^2\theta}{\csc\theta(\sec\theta\,-\,\tan\theta)}\)
\(\displaystyle \L\;\;\;= \;\frac{2\cdot\sec^2\theta\,-\,2\sec\theta\cdot\tan\theta}{\csc\theta(\sec\theta\,-\,\tan\theta)} \;=\;\frac{2\cdot\sec\theta(\sec\theta\,-\,\tan\theta)}{\csc\theta(\sec\theta\,-\,\tan\theta)} \;= \;\frac{2\cdot\sec\theta}{\csc\theta}\)
\(\displaystyle \L\:\;\;\;= \;\frac{2\cdot\frac{1}{\cos\theta}}{\frac{1}{\sin\theta}} \;= \;2\cdot\frac{\sin\theta}{\cos\theta}\)\(\displaystyle \;=\;2\cdot\tan\theta\;\;\)
. . . ta-DAA!